KARAKTERISASI SIFAT FISIK DAN AKTIVITAS ANTIOKSIDANPADA TEPUNG BUAH PEDADA (Sonneratia caseolaris) DENGAN SUHU PENGERINGAN BERBEDA - Verdiantika, Tandani Chandra; Pujiastuti, Dwi Yuli; Andriyono, Sapto (Marinade, 2022)
Pedada fruit (Sonneratia caseolaris) is a commodity of the fisheries and marine sectors that is able to prevent abrasion and as a place to live for several marine biotas. The part of the pedada fruit can be used starting from the leaves, stems, skin, and fruit. The advantages obtained are that the fruit can be directly eaten and has a variety of nutritional content of vitamins and secondary metabolites. Pedada fruit flour is able to become the substitution for flour that has high nutritional value. The role of drying temperature can improve physical and chemical properties, as well as increase the nutritional content and secondary metabolites that affect the quality of products. The research aimed to find out the physical characterization and antioxidant activity of pedada fruit flour (Sonneratia caseolaris) with different drying temperatures. This research method used the different drying temperatures of 40oC (R1), 50oC (R2), and 60oC (R3) with three repetitions. The main parameters are the characterization of physical properties which include yield tests, Particle Size Index (PSI), colour, and antioxidant activity. The supporting parameters were proximate analyses. Data analysis used Analysis of Variance (ANOVA) 1 factor and Least Significant Difference (LSD). The results showed that the physical characteristics of pedada fruit flour produced yields ranging from 8.38±0.08 to 11.31±0.10 with a Particle Size Index (PSI) above 96% in all treatments and the best colour appearance was light olive-brown at 40oC temperature. The value of antioxidant activity varies between 15.49±0.03 to 71.63±0.01 which decreases with increasing drying temperature and has a proximate analysis that is suitable for use as a substitute for consumption according to SNI. The effect of drying temperature on pedada fruit flour (Sonneratia caseolaris) had a significant effect (p